Role of Growth Differentiation Factor 15 in Lung Disease and Senescence: Potential Role Across the Lifespan - Al-Mudares, Faeq; Reddick, Samuel; Ren, Jenny; Venkatesh, Akshaya; Zhao, Candi; Lingappan, Krithika (Frontiers in Medicine, 2020)
Growth Differentiation Factor 15 (GDF15) is a divergent member of transforming growth factor-beta (TGF-β) superfamily and is ubiquitously expressed, under normal physiological conditions. GDF15 expression increases during many pathological states and serves a marker of cellular stress. GDF15 has multiple and even paradoxical roles within a pathological condition, as its effects can be dose- and time-dependent and vary based on the targeted tissues and downstream pathways. GDF15 has emerged as one of the most recognized proteins as part of the senescence associated secretory phenotype. Cellular senescence plays a major role in many lung diseases across the life-span from bronchopulmonary dysplasia in the premature neonate to COPD and idiopathic pulmonary fibrosis in aged adults. GDF15 levels have been reported to be as a useful biomarker in chronic obstructive pulmonary disease, lung fibrosis and pulmonary arterial hypertension and predict disease severity, decline in lung function and mortality. Glial-cell-line-derived neurotrophic factor family receptor alpha-like (GFRAL) in the brain stem has been identified as the only validated GDF15 receptor and mediates GDF15-mediated anorexia and wasting. The mechanisms and pathways by which GDF15 exerts its pulmonary effects are being elucidated. GDF15 may also have an impact on the lung based on the changes in circulating levels or through the central action of GDF15 activating peripheral metabolic changes. This review focuses on the role of GDF15 in different lung diseases across the lifespan and its role in cellular senescence.